The IoT gateway with active queue management - Domański, Adam; Domańska, Joanna; Czachórski, Tadeusz; Klamka, Jerzy (1944- ); Szyguła, Jakub; Marek, Dariusz (Zielona Góra: Uniwersytet Zielonogórski)
As the traffic volume from various Internet of things (IoT) networks increases significantly, the need for adapting the quality of service (QoS) mechanisms to the new Internet conditions becomes essential. We propose a QoS mechanism for the IoT gateway based on packet classification and active queue management (AQM).
Keywords: active queue management; PI controller; dropping packets; fractional calculus; IoT gateway